THE FAIR EXCHANGE® (TROCA JUSTA®): A NEW MODEL OF CLINICAL PRACTICE GUIDELINES. - Monteiro Cesnik, Vanessa (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
The study aims to present the guidelines of the Fair Exchange® (Troca Justa®) intervention, developed in the Institution O Corpo Explica® (The Body Explains®). The intervention appears as an alternative method for the treatment of emotional and physical symptoms. The proposal consists of investigating phenomena from the individual's past, as it considers that traumatic events consolidate Layered Abyss, which in turn support the Indirect Gains. The intervention is based on concepts known from the scientific literature, such as psychosomatics and synchronicity, in addition to borrowing aspects from the theories of authors such as Wilhelm Reich and Bert Hellinger, in order to build The Logic of Life® (A Lógica da Vida®), a new theoretical framework that governs the Fair Exchange® intervention. As for the applicability, the intervention is carried out 100% online and has 18 stages, considering psychometric questionnaires (which make up the five forms of the intervention process), moments of psychoeducation (through pre-recorded videos) and five synchronous sessions with professionals trained by the Institution. In addition, all the undergo an internal audit process, to maintain the quality of the intervention. The initial results showed that among people who reported suffering from some physical symptom, 66.40% reported improvement in some physical symptom during treatment (before the last session with a trained professional). Among the people who reported emotional symptoms, 82.70% reported some type of improvement up to the same moment of the Fair Exchange process. Finally, these preliminary results showed that the clients who went through the Fair Exchange® intervention showed improvement in emotional and even physical symptoms, showing that the brief therapeutic proposal presents promising results.